The Effect of Combination of Cone Drill (Zigzag) with Core Stability, Combination of Ladder Drill (Snake Jump) with Core Stability, and Speed on Agility of Futsal Players: A Factorial Experimental Design - Ilham Ilham; Raffiandy Alsyifa Putra; Apri Agus; Bafirman Bafirman; Arsil Arsil; Ridho Bahtra; Randi Kurniawan; Japhet Ndayisenga; Alexandre Sibomana (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The game of futsal, known for its high intensity and dynamic nature demanding skill and robust physical fitness, particularly in agility, presents a significant challenge. Incorporating variations of cone and ladder drills in agility training, with a focus on enhancing balance through core stability training in conjunction with speed modulation as a key factor, is believed to impact players' agility players. Despite recognizing the individual significance of these training modalities in boosting agility performance, there remains a gap in fully comprehending their combined effects during futsal engagements. This research seeks to scrutinize the group differentials in agility training, factoring in speed variations in relation to futsal players' agility levels. The study defined agility training cohorts as a combo group of cone drill with core stability and a combination group of ladder drill alongside core stability, while speed was categorized as high or low. Employing an experimental methodology with a 2 x 2 factorial design, the study enlisted 20 players aged 17.1 ± 0.76 years through random selection. Agility training, conducted thrice weekly over a six-week period, emphasized swift and dynamic movements alongside maintaining balance. Speed and agility metrics were assessed using the 30m acceleration test and Illinois agility test, then subjected to statistical scrutiny via a two-way ANOVA at a significance level of 0.05. Results revealed that both training methodologies benefited participants with elevated speed (P<0.05). Notably, agility training incorporating ladder drill exercises and core stability training exhibited superior outcomes for high-speed performers (P<0.05). Conversely, individuals with lower speed levels potentially benefitted more from a combination of ladder drill and core stability (P<0.05). These findings furnish crucial insights for futsal coaches and trainers looking to craft tailored training regimens aimed at enhancing agility performance effectively.